Analyzing The Impact of Good Governance on Public Trust: The Mediating Role of Institutional Legitimacy in Jordan’s Public Sector - Almaaitah , Mohammad Fathi; Taamneh , Mohammad M.; Ta’amneh , Abdallah Mohammad Mahmoud; Eneizan , Bilal; Banikhaled , Marie Hassan Hamad (International Journal of Accounting and Economics Studies, 2025)
This study investigated the impact of good governance on public trust in Jordan’s Public Sector, examined the mediating role of institutional legitimacy between good governance and public trust in the public organizations, and suggested a model encompassing three major ministries, three central agencies, and three public institutions. The data were collected from a stratified random sample of 383 supervisory and managerial participants via questionnaire. A Structural Equation Modelling (SEM) technique was used for data analysis. Findings revealed that (i) governance principles —transparency, accountability, and responsiveness— have a significant positive effect on public trust, (ii) institutional legitimation has a strong positive effect on public trust, (iii) institutional legitimacy significantly mediated the relationship between good governance and public trust, and (iv) the importance of strategic reforms to support transparency, improve communication, and promote inclusive public engagement. This study recommended (i) Government institutions should develop mechanisms for transparency, accountability, and participation to ensure decision-making that is in the best interests of citizens and enhance their trust. (ii) Emphasis should be placed on establishing institutional legitimacy through adherence to societal values and norms, as this is a key link between good governance and public trust.
Keywords: Accountability, Governance, Jordanian public sector, Legitimacy, Trust